Unveiling a Rare Case of Neonatal Terminal Limb Anomalies with Bilateral Toenail Agenesis and Clubfoot: A Potential Variant of Adams-Oliver Syndrome - Eesha, Eesha; Jyotsna, Jyotsna; Sud, Shyam Sunder (Journal of Neonatal Surgery, 2025)
Congenital anomalies involving terminal limb defects and nail hypoplasia are uncommon and may signify an underlying syndromic etiology. We report the case of a term female neonate born with absent great toenails bilaterally, congenital talipes equinovarus (CTEV), and radiologically absent talus on one side, along with distal phalanx deficiency. Antenatal ultrasound had indicated fetal growth restriction (FGR), two-vessel umbilical cord, and mild irregular bubble. Postnatal clinical examination, radiological evaluation, and pending genetic studies suggest a provisional diagnosis of Adams-Oliver Syndrome (AOS), a rare genetic disorder known for scalp and limb anomalies. The absence of scalp lesions, however, highlights a broader phenotypic variation. This case underlines the importance of a multidisciplinary approach, early imaging, genetic counseling, and the need to consider AOS even in the absence of classical findings.